2017
DOI: 10.1016/j.cub.2017.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Epigenetic Strategies Potentiate Gal4 Activation to Enhance Fitness in Recently Diverged Yeast Species

Abstract: Summary Certain genes show rapid reactivation after several generations of repression, a conserved phenomenon called epigenetic transcriptional memory. Following previous growth in galactose, GAL gene transcriptional memory confers a strong fitness benefit in Saccharomyces cerevisiae adapting to growth in galactose for up to 8 generations. A genetic screen for mutants defective for GAL gene memory revealed new insights into the molecular mechanism, adaptive consequences and evolutionary history of memory. A po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 61 publications
(105 reference statements)
0
29
0
Order By: Relevance
“…2016 ; Roop et al. 2016 ; Sood and Brickner 2017 ). To determine which, if any, genetic and molecular features were associated with quantitative variation in galactose growth between species, we examined 19 DNA sequence features of the GAL networks of 17 species from the family Saccharomycetaceae.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2016 ; Roop et al. 2016 ; Sood and Brickner 2017 ). To determine which, if any, genetic and molecular features were associated with quantitative variation in galactose growth between species, we examined 19 DNA sequence features of the GAL networks of 17 species from the family Saccharomycetaceae.…”
Section: Resultsmentioning
confidence: 99%
“…2013 ; Roop et al. 2016 ; Sood and Brickner 2017 ). Mutations in coding regions have been frequently shown to lead to the acquisition of novel enzymatic activities and radical modifications in specificity ( Thomson et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of galactose, Gal4 activation function is blocked by the repressor Gal80, while in the presence of galactose, Gal4 activates the transcription of genes required for galactose catabolism. Gal4 consists of an N-terminal DNA binding domain that targets the upstream activating sequence (UAS) of Gal4-regulated genes, a large central domain that likely plays a regulatory role, and a C-terminal transcription activation domain (AD) (Keegan et al, 1986; Ma and Ptashne, 1987b; Sood and Brickner, 2017; Stone and Sadowski, 1993; Wu et al, 1996). Under non-inducing conditions, Gal80 binds the Gal4 AD tightly and blocks its function (Johnston et al, 1987; Ma and Ptashne, 1987a).…”
Section: Introductionmentioning
confidence: 99%
“…These studies revealed that there can be significant variability in an initial induction leading to bimodal expression depending on the galactose concentration due to feedback loops. Zacharioudakis et al and Sood et al showed that transcriptional memory reduces this variability, allowing the population to have a uniform response during reinduction (Sood and Brickner 2017 ; Zacharioudakis et al 2007 ). Sood et al further used fluorescence-activated cell sorting (FACS) to identify a Gal1p mutant that specifically affects memory by disrupting its interaction with Gal80p.…”
Section: Using Single-cell Assays and Live-cell Observations With Linmentioning
confidence: 99%